2010
DOI: 10.1542/peds.2010-0744
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Consequences of Universal Sibling Screening for Vesicoureteral Reflux: Decision Analysis

Abstract: OBJECTIVE Our objective was to evaluate screening for vesicoureteral reflux (VUR) among siblings of patients with VUR, in terms of cost, radiation exposure, and number of febrile urinary tract infections (fUTIs) averted. METHODS We constructed a Markov model to evaluate 2 competing management options, that is, universal screening (cystographic evaluation of all siblings without symptoms) and usual care (cystographic evaluation of siblings only after fUTIs). Published data were used to inform all model inputs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…However, because the brother is only 1 year old, the probability of VUR is higher (approximately 50%). (19) The decision analysis approach shown in Figure 7 provides a formal, transparent, and orderly analytic approach to assist in decisionmaking by parents and practitioners. On the basis of these numbers, a decision may be made regarding whether this 18-month-old sibling should undergo screening at the pediatrician’s office and be scheduled for a VCUG and renal sonogram.…”
Section: Decision Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the brother is only 1 year old, the probability of VUR is higher (approximately 50%). (19) The decision analysis approach shown in Figure 7 provides a formal, transparent, and orderly analytic approach to assist in decisionmaking by parents and practitioners. On the basis of these numbers, a decision may be made regarding whether this 18-month-old sibling should undergo screening at the pediatrician’s office and be scheduled for a VCUG and renal sonogram.…”
Section: Decision Analysismentioning
confidence: 99%
“…A decision is needed on appropriate approach to his 18-month-old asymptomatic brother based on available evidence. (19)…”
Section: Figurementioning
confidence: 99%
“…Candidemia is the third most common nosocomial bloodstream infection during late-onset neonatal sepsis [ 1 ]. It affects 10 to 20% of extremely low birth weight infants and 2 to 16% of very low birth weight neonates and is responsible for 25 to 30% of morbidity in neonatal intensive care units (NICUs) [ 2 7 ]. It was reported that the infants who survive candidemia frequently have long-term neurodevelopmental impairment, which occurred in 57% of these high-risk infants [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive candidiasis is the second cause of mortality due to infectious diseases in preterm NB and represents 10% of all sepsis cases. It is the major cause of late infection in preterm NB ( 2 , 3 , 5 , 12 ) with varying incidence and high mortality ( 4 8 ) . Long hospital stay and exposure to environmental factors, as well as contact with other patients or transmission by health professionals with hands colonized with fungi are important causes of opportunistic infections ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…can be vertical, transmitted from mother to baby during birth, or horizontal, due to external contamination ( 7 , 8 ) . Other relevant risk factors are: prematurity and immaturity of the immune system, weakened physical barriers, colonization, and exposure to environmental factors, such as central venous catheter, prolonged use of endotracheal tube, H2 blockers, prolonged use of antibiotics or steroids, parenteral nutrition, long hospital stay, recent surgery, dialysis, maternal hypertension, restricted intrauterine growth, asphyxia, hospital infection and advanced maternal age at gestation ( 2 , 3 , 5 8 , 10 – 15 ) .…”
Section: Introductionmentioning
confidence: 99%